Stitches of tradition = gashkigwaaso tradition - Rendon, Marcie R. (Heartdrum, an imprint of HarperCollinsPublishers, 2024)
"As she grows up, Tatiana, a young Ojibwe girl, celebrates the big events of her life by wearing the beautiful ribbon skirts she creates with her nookomis (grandmother), a tradition connecting her to generations of her family"--